Socio-Religious Education of the Tèngka Tradition in the Madura Community - Ach. Nurholis Majid; Fitrah Sugiarto (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
The tèngka tradition that became one of Madura’s social norms containsbehavioural values and is still inherent in their social life. They believethis tradition has created a peaceful, harmonious, humorous society. Thispaper aimed to reveal the values of socio-religious education containedin the tradition and how the internalization process is strongly internalizedinto the lives of the Madurese people. This study uses qualitative methodsand data collection techniques in the form of interviews research with observations, documentation, interviews and literature studies. Thisstudy found that the tradition of tèngka did have wisdom values that areimportant to preserve, mainly as it contained Islamic teachings among thevalues of tèngkawere at-ta’âwun (mutual assistance), cooperation, socialcare, and hospitality. This study also concluded that as local wisdom, thetèngka tradition has a contributive value in the social life of the Maduresepeople, especially in creating a peaceful, harmonious, and prosperous society.This tradition survives and develops because members of the communitycarry out the process of internalization to the next generation in a personal-cognitive recognition, they also carried out in a collective-empirical-recognitionway, and finally by incidental-delegation. There are two crucial implications of this study. First, this study provides an overview of socio-religious values in the tèngka tradition as one of the local wisdom of the Madurese people. Second, this study provides an overview of the pattern of preserving local wisdom in globalization.